The Legal History Analysis of Filling the Position of Asymmetric Regional Head in the Special Region of Yogyakarta - Triwahyuningsih Triwahyuningsih (Jurnal Daulat Hukum, 2022)
This study aims to describe aspects of the legal history of filling the position of asymmetric Regional Head in the Special Region of Yogyakarta. This research is a normative legal research with a statute approach using primary and secondary legal materials and analyzed qualitatively descriptively. The results of the study indicate that the study of legal history shows that filling the position of Governor of DIY through a (asymmetric) determination does not conflict with Article 18 paragraph (4) of the 1945 Constitution and Article 18 B paragraph (1). The filling of the positions of Governor and Deputy Governor can be traced in various regional government laws that have been in force in Indonesia. In Act No. 22 of 1948 concerning the Principles of Regional Government: Article 18 paragraph (5) and (6) states: "Heads of special regions are appointed by the President from the descendants of families who ruled in the area before the Republic of Indonesia and who still control the area, with the conditions of skill, honesty and loyalty and keeping in mind the customs of that area. Act No. 1 of 1957, Act No. 18 of 1965, the Basic Law on Regional Government has changed due to adapting to the latest political developments, but with regard to filling the positions of Governor and Deputy Governor of DIY, it remains through appointment and is not bound by time (for life). During the New Order, Act No. 5 of 1974. Finally, based on Act No. 13 of 2012 concerning the Privileges of the Special Region of Yogyakarta Article 24, DPRD DIY stipulates Sultan Hamengku Buwono who reigns as Governor.